Godsdiens en Christelike teologie in die skadu van menslike outonomie: wetenskapsfilosofiese verkenninge - Richards, W. J. (Acta Theologica, 2001)
The phenomenon of religion was often regarded in “scientific” religious studies as something of which the essence and origin was purely human. Psychologists and sociologists of religion inter alia often thought they could fully explain religion in pure human and scientific terms. Later on even historians and phenomenologists of religion etc became convinced (on similar immanentistic grounds) that there was more to it, and that other disciplines such as philosophy and theology were needed in the last resort to come closer to an explanation by introducing transcendental evidence and views. Religion, they were convinced, could not be explained in terms of evidence derived from mere facts or disciplines operating on purely empirical levels within a one-dimensional world. Christianity, more particularly since modern times (dating from the 19th century especially), had to face up to rather extreme rationalistic views, more especially after the time of Barth. Sections 4 and 5 of this article deal with these trends as well as the opposition offered by theologians coming e g from the Reformational tradition. Much solid work has been done in which attention has been paid to the detrimental influence exerted by the spirit of the times, however often without giving any suggestions regarding possible approaches to present day cultural trends. Untouched remained also the questions how to harness culture as such, how to use philosophy and science in the service of reformation and for the solution of practical problems outside the immediate scope of the church as such, while at the same time, even if only indirectly, supporting the aims of the Church. Science and culture can hardly be left unconvered to be instruments (powerful ones) in the hands of secularisation alone. In the last section an effort is made to show how Reformed philosophy (preliminary as it may be, yet starting, as it does, from the same belief in God) tries to counter undesirable and detrimental trends in culture, while at the same time stimulating those which can honour God through service in His Kingdom. Hopefully the ideals cherished by the church will also benefit from such efforts in a wider field.